STUDI KEMAMPUAN KOMPONEN LABA-RUGI SEBAGAI PREDIKTOR KOMPONEN ARUS KAS MASA DEPAN - Syamsul Rijal (AkMen JURNAL ILMIAH, 2020)
Cash flow component prediction are useful for internal and external parties to minimize the risk when they make necessary economic decisions. Earnings and cash flow are indicators of the performance and quality of management in managing the company in a certain period. This study aims was to test the relationship of the ability of earnings component in predicting each cash flow component. The first alternative hypothesis is earnings component have predictive ability to cash flow from operations. Second, earnings component have predictive ability to cash flow from investment activities. Lastly, earnings component have predictive ability to cash flow form financing activities. This research using statistical method linear regression by using pooled data, which is consist of 40 cross-sectional observations and 3 time series observations. Dependent variable is cash flow operations change (∆CFOt) or cash flow from investing activities changes (∆CFIt) or cash flow from financing activities changes ((∆CFFt) from the period (2017-2016) to (2019-2018). Independent variables are gross profit changes (∆GPt-1), operations profit changes (∆OPt-1) and net profit changes (∆NIt-1) from (2016-2015) to (2018-2017). The conclusion from statistical analysis shows that: first, earnings component are significant in predicting cash flow from operations one year ahead. Second, earnings component were not significant in predicting cash flow from investment activities one year ahead. Lastly, earnings component are significant in predicting cash flow from financing activities one year ahead.